THE INFORMAL LEARNING ATMOSPHERE EXPOSED TO AN EFL LEARNER WITH ADHD IN VOCABULARY MASTERY - Suhani, Rizka; Susilawati, Endang; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study was aimed to identify the components of the informal learning atmosphere exposed to the EFL learner with ADHD who had a surprising capability in vocabulary mastery and to describe the ADHD learner"™s engagements with the informal learning atmosphere in mastering vocabulary. This study was conducted using case study approach with semi-structured interview questions and field notes as the tools of collecting data. To collect sufficient data to analyze this study, the researcher did interviews and observations. After conducting interviews and observations, the researcher found out that three major components of informal learning atmosphere had been exposed to this learner started from his early age. There were everyday family setting, autonomous learner, and visual, audio-visual and digital media taken important parts in developing his language development, especially in his vocabulary mastery. Unfortunately, other components of informal learning atmosphere which should take place in the school could not be analyzed due to the lack of English language exposures in his special needs school. Furthermore, the researcher found that the ADHD learner"™s engagements with an informal learning atmosphere had maximized his strengths and minimized his weaknesses of his ADHD symptoms in enhancing his language skills, especially in mastering vocabulary.